Paisagem e denúncia: A paisagem contemporânea além da contemplaçãoestética da natureza - Jose Paulo das Neves (2009)
This study constitutes in an effort to elucidate why contemporary artists still work with landscape. It appears in western culture almost at the same time as the idea of art that we share today, around the XIV century, at the beginning of modernity. Landscape has become extremely ordinary by the media since the second part of the XX century. It serves to everything. My investigation tries to find out what still can move artists interests in landscape, in a world permanently eager for novelties,and how this is expressed in their production. Among the various evidences I came to, I choose one that indicates the possibility of landscape, going beyond esthetics questions, being appropriated by the idea of denouncement. The methodological procedures followed in this study is bibliographic review and contemporary artworks analysis .